Overcoming climate change adaptation barriers: A study on food–energy–water impacts of the average American diet by demographic group. (25th March 2019) - Bozeman, Joe F.; Bozeman, Rayne; Theis, Thomas L.
Abstract: Effectively adapting to climate change involves overcoming social and ecological system barriers. The present study uses a three‐phase adaptation framework to propose adaptation strategies aimed at overcoming socioecological barriers of the food–energy–water (FEW) nexus. Cradle‐to‐farm‐gate land, greenhouse gas (GHG), and water impacts—that derive from food consumption in the United States—are analyzed and differentiated by major demographic groups (Black, Latinx, and White). Results indicate that the White demographic yields the highest per capita GHG (680 kg of CO2  eq⋅year −1 ) and water impacts (328, 600 L⋅year −1 ) from food consumption, whereas the Black demographic yields the highest per capita land impacts (1, 770 m 2 ⋅year −1 ) from food consumption. Our findings suggest that obtaining data with the intention of building consensus across sociodemographic lines overcomes barriers in the understanding phase, leading to increased social receptivity for many planning and managing phase processes. Specifically, we find that identifying and developing leaders who possess the cognitive and interpersonal capacity to manage many variables and stakeholders is key to assessing and selecting adaptation options in the planning phase. We also propose using government programming to encourage environmentally friendly food purchasing behavior. Then, we discuss how our proposals could be used in adaptation feasibility and evaluation activities in the managing phase. In all, these findings facilitate the development of improved climate change adaptation and policy by satisfying the understanding phase of the climate change adaptation framework, establishing a cross‐disciplinary methodological approach to addressing socioecological problems, and providing useful FEW impact data for FEW nexus and climate change researchers.